Enhancing farmers’ income through crop diversification - Yadava, N. D.; Rathore, V. S.; Soni, M. L. (Indian Farming, 2018)
Crop diversification provided an opportunity to farmers for choosing more number of crops as per their available resources, facilities for cropping and their need as well as requirements of food and fodder. Inclusion of perennials in the system also provides an insurance against complete crop failure providing multiple produce in one time from same piece of land. The more number of high value crops are able to utilize the resources in better way providing higher income to the farmers.